Genes, the environment and personalized medicine. (6th June 2014) - Carlsten, Chris; Brauer, Michael; Brinkman, Fiona; Brook, Jeffrey; Daley, Denise; McNagny, Kelly; Pui, Mandy; Royce, Diana; Takaro, Tim; Denburg, Judah
<x xml:space="preserve">Abstract</x> In their enthusiasm to implement genomics‐based personalized medicine, researchers, clinicians and policymakers have missed two crucial considerations: environmental factors and epigenetics. Both of these must be crucial components of future research into tailored health solutions for individuals. <boxed-text content-type="graphic" id="embr201438480-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>